Health Service Utilisation and Out of Pocket Expenditure Pattern in a Defined Rural Population of Tumkur, India - Shwetha TM; Ashok J; Rajesh SS; MS, Rajanna (National Journal of Community Medicine, 2018)
Introduction: Universal health coverage: The provision of, and access to, high-quality health services; and financial risk protection for people who need to use these services1. Through this study we want to assess where we stand in terms of health service utilization and out of pocket expenditure in view of universal health coverage. The research was conducted to study socio demographic profile of the population; to know health service utilization pattern of the population; and to assess the out of pocket expenditure towards health care. Methodology: It is a Cross –sectional study conducted in Tumkur district of Karnataka 2014 -15. Structured questionnaire was used to collect the data by interview method. Data was entered in Microsoft Excel and analysed using Epi Info™ 7.1.1.14. Results: The Private health services were one of the major sources of overall health services Mean out of pocket expenditure was 744 Rs. The mean out of pocket expenditure for Out Patient care , for chronic illness , In patient care was 135, 44 and 117 Rupees respectively. Medicines are the major part of out of pocket expenditure . Conclusion: The Private health Care services were one of the major sources of health services followed by Government. Medicine was the major component for which the money was spent.